Analysis of the legislative reform proposals for credit unions of Trinidad and Tobago - Khan, Glenn A. ([CCMS] [St. Augustine]TT, 2001)
Focuses on areas such as capacity and power; financial services; capital and liquidity; Directors and Credit Committee; regulator of credit unions; deposit insurance; and, licencing of credit unions.